Captain Cat - Hoff, Syd, 1912-2004. (New York : HarperTrophy, 1993)
A cat makes friends with a soldier and learns about military life when he joins the army.
"PreS-grade 1"--Cover.
1.7
K-3
K-3
Elem. School Library Collection
School Library Journal
Keywords: Cats -- Fiction; Cats -- Fiction; Readers (Elementary)